How Local Bureaucrats Utilize Non-Governmental Political Actors in Their Struggle to Reach Political Post - Budiman, Arif; Yuwanto; Hidayat, Nur; Alfirdaus, Laila Kholid (South Eastern European Journal of Public Health, 2024)
The opportunity for local bureaucrats to transform into public officials through local elections in Indonesia is wide open. With technical-administrative expertise, control over financial resources and personnel development, high social status in the community, and roles in formulating public policies within government organizations, bureaucrats can easily rally political support from both governmental and non-governmental political actors. Effective political communication links with regional heads and deputies, as well as legislators, can be more easily established by relying on these sources of power. However, under certain conditions, these variables are not sufficient to convince the political parties to immediately provide support, particularly when the bureaucrat touted as a candidate is known to have a poor image and performance record in the eyes of political authorities. Using a descriptive-phenomenological research method, this study seeks to explore and find other factors utilized by bureaucrats to convince political parties to support their candidacy for deputy head of region. Through interviews with key informants and significant others, as well as a literature review relevant to the research substance, it was found that in addition to political actors within the government, there are other political actors outside the government such as charismatic community leaders and heads of social organizations in a paternalistic society that can help bureaucrats gain political party support in their candidacy as deputies head of region in Indonesia.